2003
DOI: 10.1007/s00134-003-1651-0
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria does not reflect increased systemic capillary permeability in septic shock

Abstract: In this study patients in septic shock with significantly elevated EVLW had normal urinary M:Cr, and there was no correlation between M:Cr and EWLV, and PaO(2)/FIO(2). Therefore based on the current results routine measurements of microalbuminuria to determine endothelial permeability cannot be recommended in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…In healthy individuals, orosomucoid is present in urine in amounts 10-to 20-fold lower than albumin, but in our sepsis patients, orosomucoid excretion reached rates equal to or higher than those of albumin. The observed increase in urinary albumin excretion to amounts within the microalbuminuric range are in quantitative agreement with previous reports on sepsis patients (8 ) and on patients undergoing abdominal surgery (9 ).…”
Section: Description and Classificationsupporting
confidence: 92%
“…In healthy individuals, orosomucoid is present in urine in amounts 10-to 20-fold lower than albumin, but in our sepsis patients, orosomucoid excretion reached rates equal to or higher than those of albumin. The observed increase in urinary albumin excretion to amounts within the microalbuminuric range are in quantitative agreement with previous reports on sepsis patients (8 ) and on patients undergoing abdominal surgery (9 ).…”
Section: Description and Classificationsupporting
confidence: 92%
“…Although urinary albumin excretion is an important hallmark of septic ARF [2,26,33], the molecular basis of albuminuria is not fully understood. In this regard, we reported that the loss of nephrin, another key molecule of SD [9], becomes evident during sepsis through a loss in nuclear localization of WT1, a key transcriptional factor of nephrin [ 16].…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis-mediated renal injury is a typical phenotype of ARF that is associated with albuminuria [2,33]. During the sepsis, glomerular thrombosis becomes evident via up-regulations of inflammatory cytokines, and then local permeability and hypoxia enhance renal damage, associated with a loss in renal blood flow [26,30]. Even under low glomerular filtration, albuminuria is often noted in septic patients [2,33] and in rodents [31].…”
mentioning
confidence: 99%
“…Postulated mechanisms include acute changes in glomerular capillary permeability 52 and inflammatory insults. 53 In addition, clinical situations that lead to AKI may result in albuminuria due to diminished reabsorption by the injured proximal tubules. The potential utility of albuminuria as a test for the early diagnosis of AKI has not been systematically evaluated.…”
Section: Tubular Proteinuria For the Diagnosis Of Akimentioning
confidence: 99%